Road Handling Priority Analysis Using Provincial/District Roads Management System Application and Analytical Hierarchy Process Method - Farida, Nur Aini; Nugroho, Laksono Djoko; Muhammadun, Haris (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2025)
This study aims to determine the priority of road handling in East Java Province by integrating the Provincial/District Roads Management System (PKRMS) application and the Analytical Hierarchy Process (AHP) method. Road condition data is obtained from PKRMS, including the physical condition of the road, traffic volume, and other parameters. The main criteria used in the AHP analysis are road condition, volume capacity ratio (VCR), connectivity, land use and priority areas of East Java Province. Each criterion was assessed and weighted based on its level of importance to produce road handling priorities.  The results showed that the integration of PKRMS and AHP was able to produce a more accurate order of road handling priorities in accordance with strategic needs. In the UPT PJJ Surabaya Road Section, road improvement priorities are arranged based on the Triggered Priority Index (TPI) value obtained from the combined analysis. This research also provides cost estimates for each road section, which helps with more efficient budget planning.  With this approach, it is expected that road management in East Java Province can be carried out more effectively, support inter-regional connectivity, and have a positive impact on economic growth.